Cloning and Expression of Xylitol Dehydrogenase Enzyme from Spathaspora passalidarum in Saccharomyces cerevisiae - Mamoori, Yaseen I; Al-Jelawi, Majed H; Yahya, Abdul Ghani I (Al-Nahrain Journal of Science, 2018)
Spathaspora passalidarum is a natural xylose fermenting yeast that have the fungal pathway for converting xylose to ethanol. The second enzyme in this pathway is NAD+- dependent Xylitol dehydrogenase which converts xylitol to xylulose. In this study, the sequence of the nucleotides for XYL2 gene is found in JGI site. It consists of 1098 bp and code for 365 amino acids. The forward and reverse primers were designed with restriction sites on the 5` termini which are SacII and NotI restriction enzyme respectively using Lasergene 9.0 program. Genomic DNA was isolated and purified from S .passalidarum and amplified using PCR and it cloned into pSN303 resulting of the pYIM2 plasmid. Then it is transformed into Escherichia coli. This plasmid was isolated from E. coli and retransformed into S. cerevisiae and transformant is called YJTY2. Results showed that enzyme specific activities with NAD+ as cofactors were 2.32 and 0.0 U/mg for S. cerevisiae YJTY2 and S. cerevisiae (CENPK2.1D) respectively. The enzyme did not show any activity with NADP+ as a cofactor. This enzyme is NAD+ dependent and can be used in combination with xylose reductase in S. cerevisiae to be able to ferment xylose. S. passalidarum